Utility of Normal Findings on Electrocardiogram and Echocardiogram in Subjects ≥65 Years - Venkatesh, Sanjay; O'Neal, Wesley T.; Broughton, Stephen T.; Shah, Amit J.; Soliman, Elsayed Z. (The American journal of cardiology, 2017)
The lack of abnormalities found on noninvasive cardiac testing possibly improves cardiovascular disease (CVD) risk stratification efforts and conveys reduced risk despite the presence of traditional risk factors. This analysis included 3,805 (95% white and 61% women) participants from the Cardiovascular Health Study (CHS) without baseline CVD. The combination of a normal electrocardiogram (ECG) and echocardiogram was assessed for the development of CVD. A normal ECG was defined as the absence of major or minor Minnesota code abnormalities. A normal echocardiogram was defined as the absence of contractile dysfunction, wall motion abnormalities, or abnormal left ventricular mass. Cox regression was used to compute the 10-year risk of developing coronary heart disease, stroke, and heart failure events. There were 1,555 participants (41%) with normal findings on both measures. After accounting for traditional CVD risk factors, a protective benefit was observed for all outcomes among participants who had normal ECG and echocardiographic findings (coronary heart disease: hazard ratio [HR] 0.56, 95% confidence interval [CI] 0.46, 0.69; stroke: HR 0.57, 95% CI 0.43, 0.76; heart failure: HR 0.36, 95% CI 0.29, 0.41). The addition of this normal profile resulted in significant net reclassification improvement of the Framingham risk score for heart failure (net reclassification improvement 4.3%, 95% CI 1.0, 8.0). In conclusion, normal findings on routine noninvasive cardiac assessment identify subjects in whom CVD risk is low.